Investigation of the Bonding Formation of a Plasma-Sprayed Cast Iron Splat on a Preheated Aluminum Substrate Using an Experimentally Based Numerical Simulation Method - Xing, Ya-Zhe; Wang, Ke; He, Li; Liu, Zhang; Chen, Yong-Nan (Journal of thermal spray technology, 2020)
In this study, the bonding formation of the cast iron splat deposited on a preheated aluminum substrate by atmospheric plasma spraying was investigated using a finite element method based on a heat transfer model built in a cylindrical coordinate system. To enhance the accuracy of calculations, thermal contact resistance ( R th ) of the contact interface was incorporated into the calculation. A precise R th value was obtained using a well-established relationship. The diameter of grains in the splat was determined by atomic force microscopy analysis. Furthermore, the physical parameters of the cast iron and the aluminum at different temperatures used in the simulation were calculated according to the composition of the materials. The calculations indicated that the interface temperature was below the substrate melting point during the entire observation period, confirming that no melting of the aluminum substrate had occurred. Thus, the formation of splat–substrate metallurgical bonding was attributed to the enhanced interface temperature and plastic deformation rather than the melting of the substrate surface.